2012
DOI: 10.2514/1.c031913
|View full text |Cite
|
Sign up to set email alerts
|

Landing-Gear Drop-Test Rig Development and Application for Light Airplanes

Abstract: A drop-test rig is developed for the landing gear of a light multifunctional amphibious airplane based on its drop-test specifications. Several key technologies (including the schematic design of the light-aircraft drop test, the control-system design for the drop test, the high-speed turn of the wheel, the accurate lifting of the drop system, design of the measuring platform, and the imitation of the runway) are studied. Simultaneously, the system can realize accurate measurement and conduct the light-aircraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The bifurcation analysis is applied to determine the optimum value of the spring force used to unlock the landing gear at the beginning of the retraction sequence. Lastly, the drop test complying with the ASTM f-2245 (Abramowitz et al , 1999) is demonstrated to verify and confirm the strength and durability of the novel retractable landing gear (Xue et al , 2012).…”
Section: Introductionmentioning
confidence: 93%
“…The bifurcation analysis is applied to determine the optimum value of the spring force used to unlock the landing gear at the beginning of the retraction sequence. Lastly, the drop test complying with the ASTM f-2245 (Abramowitz et al , 1999) is demonstrated to verify and confirm the strength and durability of the novel retractable landing gear (Xue et al , 2012).…”
Section: Introductionmentioning
confidence: 93%
“…The parameters should be simulated during the drop test including landing weight, angle of attack, sinking velocity, forward velocity, and wing aerodynamic force of the aircraft [25].…”
Section: Drop Test Working Principlementioning
confidence: 99%
“…The Lernbeiss model was then revised and improved by Kong, based on drop-impact analysis and experiments conducted on a smart UAV landing system [17]. LMS ® analysis software for multi-body dynamics was used by Xue and Yu to build a coupled rigid-flexible simulation model of light aircraft main landing gear, showing very good capability in terms of drop-test load estimation [18].…”
Section: Introductionmentioning
confidence: 99%